The microRNA miR-7 regulates Tramtrack69 in a developmental switch in Drosophila follicle cells. - Huang, Y.C.; Smith, L.; Poulton, J.; Deng, W.M. (Development, 2013)
Development in multicellular organisms includes both small incremental changes and major switches of cell differentiation and proliferation status. During Drosophila oogenesis, the follicular epithelial cells undergo two major developmental switches that cause global changes in the cell-cycle program. One, the switch from the endoreplication cycle to a gene-amplification phase, during which special genomic regions undergo repeated site-specific replication, is attributed to Notch downregulation, ecdysone signaling activation and upregulation of the zinc-finger protein Tramtrack69 (Ttk69). Here, we report that the microRNA miR-7 exerts an additional layer of regulation in this developmental switch by regulating Ttk69 transcripts. miR-7 recognizes the 3' UTR of ttk69 transcripts and regulates Ttk69 expression in a dose-dependent manner. Overexpression of miR-7 effectively blocks the switch from the endocycle to gene amplification through its regulation of ttk69. miR-7 and Ttk69 also coordinate other cell differentiation events, such as vitelline membrane protein expression, that lead to the formation of the mature egg. Our studies reveal the important role miR-7 plays in developmental decision-making in association with signal-transduction pathways.